2011
DOI: 10.1136/bjophthalmol-2011-300677
|View full text |Cite
|
Sign up to set email alerts
|

Reaction time as a measure of enhanced blue-light mediated cognitive function following cataract surgery

Abstract: The results suggest that improved blue-light transmission following cataract surgery has a beneficial effect on cognitive function. We advocate the RTT as an objective platform for exploring these benefits in large sample randomised controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
(18 reference statements)
2
11
0
Order By: Relevance
“…A faster reaction time was associated with a thinner RNFL thickness (p < 0.001) and this stayed significant in the multivariable model for average RNFL (p = 0.01), and for the inferior and temporal quadrants (p = 0.01 and p = 0.04 respectively). As cataract surgery has been reported to improve reaction times 10 , we compared the reaction time in the 63 pseudophakic participants to that of 126 age-matched individuals without cataract surgery (case:control ratio of 1:2). There was no difference between the two groups (mean of 630 ms and 632 ms respectively, p = 0.8).…”
Section: Resultsmentioning
confidence: 99%
“…A faster reaction time was associated with a thinner RNFL thickness (p < 0.001) and this stayed significant in the multivariable model for average RNFL (p = 0.01), and for the inferior and temporal quadrants (p = 0.01 and p = 0.04 respectively). As cataract surgery has been reported to improve reaction times 10 , we compared the reaction time in the 63 pseudophakic participants to that of 126 age-matched individuals without cataract surgery (case:control ratio of 1:2). There was no difference between the two groups (mean of 630 ms and 632 ms respectively, p = 0.8).…”
Section: Resultsmentioning
confidence: 99%
“…Although we do not exclude that aged subjects with sleep and circadian alterations, or with cataract, might have a decreased non-visual sensitivity to light, there is no clinical evidence that healthy older individuals have a decreased non-visual sensitivity to light. Indeed, it has been reported that only half of cataract patients suffer from poor sleep, and that increased light transmission after cataract surgery [47] improves sleep quality [80] and decreases psychomotor reaction time [81]. On the other hand, patients with normal sleep quality show no difference in their sleep following cataract surgery [80], nor in their melatonin secretion, sleep parameters or sleepiness [82].…”
Section: Discussionmentioning
confidence: 99%
“…The RT task is performed on a validated purpose-built electronic device of the kind first used in the Health and Lifestyle Study18 and recently used in the pilot study 8. The participant is tested at a desktop under standard illumination and given standardised instructions for performing the test by a masked researcher.…”
Section: Methodsmentioning
confidence: 99%